If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4t + -24 + 6t = 10t + 15 + -12 Reorder the terms: -24 + 4t + 6t = 10t + 15 + -12 Combine like terms: 4t + 6t = 10t -24 + 10t = 10t + 15 + -12 Reorder the terms: -24 + 10t = 15 + -12 + 10t Combine like terms: 15 + -12 = 3 -24 + 10t = 3 + 10t Add '-10t' to each side of the equation. -24 + 10t + -10t = 3 + 10t + -10t Combine like terms: 10t + -10t = 0 -24 + 0 = 3 + 10t + -10t -24 = 3 + 10t + -10t Combine like terms: 10t + -10t = 0 -24 = 3 + 0 -24 = 3 Solving -24 = 3 Couldn't find a variable to solve for. This equation is invalid, the left and right sides are not equal, therefore there is no solution.
| 5(x+2)=4(2x-2) | | -2t^3+12t^2+600=0 | | 10-8x^2=170 | | 324+3x=36+6x | | c(7+x)=8 | | 3(x+10)=2(5x-15) | | a(x-2)=b | | w+L=4 | | 210000-6y=4y+40000 | | 5w=3L | | 49=x/((0.09375-x)^2) | | 2x+3y=x+5y | | 171=x+2x+(x+27) | | 4/5=n-9/3 | | -2(-8x+9)-6y=2(x-1)-4 | | 2(a^2)=324 | | 0.7/1.2=6.4/n | | 13x-4=2(-x-4y) | | -2(x+4)=4x+40 | | -7/3x+5/3x=-2/9 | | -6x-14=-2(x+5) | | -9+14r=4r-3-16 | | 3/8=n/12 | | 4(x+5)+3(x+3)=2(x+15)+4 | | 20n/20=68/20 | | -38=8(x-4)-2x | | 2q+3=5q-9 | | 21=x^2-16x+0 | | 38=-4x+6(x+7) | | -4=-3x+8(x-3) | | 5+4y=y-8 | | -2u^2+1+u=0 |